Strengthening Supply Chain for Post COVID-19 Food Security: An Exploratory Research Review - Harianto; Feryanto; Herawati; Rifin, Amzul (The Indonesian Forestry Certification Cooperation, 2022)
COVID-19 has had a significant impact on food supply chains at both domestic and global levels. At the same time, Indonesia's food security index experienced a significant decline. This study presents an exploratory approach-based research review aiming at identifying problems occurring along food supply chain post COVID-19 pandemic, and at examining possible policies, studies and research needed to improve food security. In addition to relevant previous studies, the authors analysed data from the Indonesian Central Statistics Agency (BPS) and Bank of Indonesia (BI). A number of problems and issues pertinent to Indonesia’s food supply chain that may adversely affect food security are identified and a post COVID-19 “exit strategy” to strengthen food supply chain is explored.